Knock‐in mouse model of alternating hemiplegia of childhood: Behavioral and electrophysiologic characterization. (19th December 2014) - Hunanyan, Arsen S.; Fainberg, Nina A.; Linabarger, Molly; Arehart, Eric; Leonard, A. Soren; Adil, Syed M.; Helseth, Ashley R.; Swearingen, Amanda K.; Forbes, Stacy L.; Rodriguiz, Ramona M.; Rhodes, Theodore; Yao, Xiaodi; et al.
Summary Objectives Mutations in the ATP1α3 subunit of the neuronal Na+/K+‐ATPase are thought to be responsible for seizures, hemiplegias, and other symptoms of alternating hemiplegia of childhood (AHC). However, the mechanisms through which ATP1A3 mutations mediate their pathophysiologic consequences are not yet understood. The following hypotheses were investigated: (1) Our novel knock‐in mouse carrying the most common heterozygous mutation causing AHC (D801N) will exhibit the manifestations of the human condition and display predisposition to seizures; and (2) the underlying pathophysiology in this mouse model involves increased excitability in response to electrical stimulation of Schaffer collaterals and abnormal predisposition to spreading depression (SD). Methods We generated the D801N mutant mouse (Mashlool, Mashl+/−) and compared mutant and wild‐type (WT) littermates. Behavioral tests, amygdala kindling, flurothyl‐induced seizure threshold, spontaneous recurrent seizures (SRS), and other paroxysmal activities were compared between groups. In vitro electrophysiologic slice experiments on hippocampus were performed to assess predisposition to hyperexcitability and SD. Results Mutant mice manifested a distinctive phenotype similar to that of humans with AHC. They had abnormal impulsivity, memory, gait, motor coordination, tremor, motor control, endogenous nociceptive response, paroxysmal hemiplegias, diplegias, dystonias, and SRS, as well as predisposition to kindling, to flurothyl‐induced seizures, and to sudden unexpected death. Hippocampal slices of mutants, in contrast to WT animals, showed hyperexcitable responses to 1 Hz pulse‐trains of electrical stimuli delivered to the Schaffer collaterals and had significantly longer duration of K+‐induced SD responses. Significance Our model reproduces the major characteristics of human AHC, and indicates that ATP1α3 dysfunction results in abnormal short‐term plasticity with increased excitability (potential mechanism for seizures) and a predisposition to more severe SD responses (potential mechanism for hemiplegias). This model of the human condition should help in understanding the molecular pathways underlying these phenotypes and may lead to identification of novel therapeutic strategies of ATP1α3 related disorders and seizures.